(untitled) (Amsterdam,Boston, Mass., 2006)
Recent corporate events have exposed the frequency and consequences of poor system security implementations and inadequate protection of private information. In a world of increasingly complex computing environments, myriad compliance regulations and the soaring costs of security breaches, it is economically essential for companies to become proactive in implementing effective system and data security measures. This volume is a comprehensive reference for understanding security risks, mitigations and best practices as they apply to the various components of these business-critical computing environments.
Keywords: Client/server computing,Hewlett-Packard computers,Máy tính khách/Chủ; Security measures,Security measures,Mức độ an ninh